Modeling Human Retinal Development with Patient‐Specific Induced Pluripotent Stem Cells Reveals Multiple Roles for Visual System Homeobox 2. (June 2014) - Phillips, M. Joseph; Perez, Enio T.; Martin, Jessica M.; Reshel, Samantha T.; Wallace, Kyle A.; Capowski, Elizabeth E.; Singh, Ruchira; Wright, Lynda S.; Clark, Eric M.; Barney, Patrick M.; Stewart, Ron; Dickerson, Sarah J.; et al.
Abstract : Human induced pluripotent stem cells (hiPSCs) have been shown to differentiate along the retinal lineage in a manner that mimics normal mammalian development. Under certain culture conditions, hiPSCs form optic vesicle‐like structures (OVs), which contain proliferating progenitors capable of yielding all neural retina (NR) cell types over time. Such observations imply conserved roles for regulators of retinogenesis in hiPSC‐derived cultures and the developing embryo. However, whether and to what extent this assumption holds true has remained largely uninvestigated. We examined the role of a key NR transcription factor, visual system homeobox 2 (VSX2), using hiPSCs derived from a patient with microphthalmia caused by an R200Q mutation in the VSX2 homeodomain region. No differences were noted between (R200Q)VSX2 and sibling control hiPSCs prior to OV generation. Thereafter, (R200Q)VSX2 hiPSC‐OVs displayed a significant growth deficit compared to control hiPSC‐OVs, as well as increased production of retinal pigmented epithelium at the expense of NR cell derivatives. Furthermore, (R200Q)VSX2 hiPSC‐OVs failed to produce bipolar cells, a distinctive feature previously observed in Vsx2 mutant mice. (R200Q)VSX2 hiPSC‐OVs also demonstrated delayed photoreceptor maturation, which could be overcome via exogenous expression of wild‐type VSX2 at early stages of retinal differentiation. Finally, RNAseq analysis on isolated hiPSC‐OVs implicated key transcription factors and extracellular signaling pathways as potential downstream effectors of VSX2‐mediated gene regulation. Our results establish hiPSC‐OVs as versatile model systems to study retinal development at stages not previously accessible in humans and support the bona fide nature of hiPSC‐OV‐derived retinal progeny. Stem Cells 2014;32:1480–1492